Cerebellar Ataxia Followed by Stiff Person Syndrome in a Patient with Anti-GAD Antibodies - Sinali O. Seneviratne; Katherine A. Buzzard; Belinda Cruse; Mastura Monif (Case Reports in Immunology)
Anti-GAD antibody syndrome is a result of the production of antibodies against glutamic acid decarboxylase (GAD), the main enzyme responsible for the production of gamma-aminobutyric acid (GABA). Several neurological manifestations including cerebellar ataxia and stiff person syndrome have been reported in association with anti-GAD antibodies. In this paper, we present a case of a young woman with anti-GAD antibodies who initially presented with cerebellar ataxia followed by stiff person syndrome three and a half years later. Having both cerebellar ataxia and stiff person syndrome is a rare occurrence in anti-GAD antibody syndrome. We emphasise the importance of long-term follow-up of patients with anti-GAD antibody syndrome, as delayed neurological manifestations can occur.